2017
DOI: 10.1002/jcb.26236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TET1 regulating MGMT on chemotherapy resistance of oral squamous cell carcinoma stem cells

Abstract: The study was to evaluate the effect of ten-eleven translocation 1 (TET1) regulating o6-methylguanine-DNA methyltransferase (MGMT) in chemotherapy resistance of oral squamous cell carcinoma (OSCC) stem cells. OSCC stem cells were divided into the blank, negative control (NC), TET1-siRNA, TET1-siRNA + MGMT-OE, and MGMT-OE groups. Methylation-specific polymerase chain reaction (MSP), qRT-PCR and Western blotting were conducted to detect the methylation status of MGMT, expressions of TET1, MGMT, ABCG2, and Oct-4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…[28][29][30][31] Several studies have reported that dysregulation of DNA methylation can promote oncogene expression and chemotherapy resistance. [32][33][34] In the present study, we found CSF2 demethylation in the promoter sites in both colon and rectal cancer tissues. These results suggested that CSF2 demethylation resulted in increased CSF2 expression in CRC.…”
Section: Discussionsupporting
confidence: 66%
“…[28][29][30][31] Several studies have reported that dysregulation of DNA methylation can promote oncogene expression and chemotherapy resistance. [32][33][34] In the present study, we found CSF2 demethylation in the promoter sites in both colon and rectal cancer tissues. These results suggested that CSF2 demethylation resulted in increased CSF2 expression in CRC.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, higher levels of TET and PML were associated with better overall survival of HNSCC patients (Song et al 2018). Wang et al (2018b) showed that a decreased expression of TET-1 in OSCC may lead to increased promoter methylation of MGMT, and enhanced the sensitivity of OSCC stem cells to chemotherapeutics like cisplatin.…”
Section: Tetmentioning
confidence: 99%
“…Xi Han et al found that TET1 expression resulted in resistance to cisplatin, and that one of the targets of TET1 action was vimentin involved in partial epithelial‐to‐mesenchymal (EMT) in ovarian cancer . Wei Wang et al provided evidence that decreased expression of TET1 may strengthen the sensitivity of oral squamous cell carcinoma stem cells to chemotherapeutics by stimulating MGMT promoter methylation to suppress MGMT mRNA expression . However, research revealed that gemcitabine‐resistant CCA cells displayed not only MDR but also enhanced invasiveness .…”
Section: Discussionmentioning
confidence: 99%